The New Left : six critical essays / / edited by Maurice Cranston - Cranston, Maurice William
En la sobrecubierta: "On Che Guevara, Jean-Paul Sartre, Herbert Marcuse, Frantz Fanon, Black Power, R.D. Laing" | Incluye referencias bibliográficas